2019
DOI: 10.1063/1.5094428
|View full text |Cite
|
Sign up to set email alerts
|

A quartz amplifier for high-sensitivity Fourier-transform ion-cyclotron-resonance measurements with trapped ions

Abstract: Single-ion sensitivity is obtained in precision Penning-trap experiments devoted to light (anti)particles or ions with low mass-to-charge ratios, by adding an inductance coil to an amplifier connected to the trap, both operated at 4 K. However, single-ion sensitivity has not been reached on heavy singly or doubly charged ions. In this publication, we present a new system to reach this point, based on the use of a quartz crystal as an inductance, together with a newly developed broad-band (BB) amplifier. We det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The experiments reported here have been carried out with the TRAPSENSOR openring Penning trap [18] and the quartz amplifier described in Ref. [9]. Calcium atoms are evaporated from an oven and collimated through a 1-mm diameter hole to reach an area close to the center of the trap, where they are photoionized using two laser beams (Fig.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments reported here have been carried out with the TRAPSENSOR openring Penning trap [18] and the quartz amplifier described in Ref. [9]. Calcium atoms are evaporated from an oven and collimated through a 1-mm diameter hole to reach an area close to the center of the trap, where they are photoionized using two laser beams (Fig.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…with Very recently we have reported the first experimental results utilizing quartz resonators for measurements of ν + of stored 40 Ca + ions [9] using the Fourier-Transform Ion-Cyclotron-Resonance (FT-ICR) technique [10,11], and performed the first mass measurements using a quartz through a ν + measurement on 206,207 Pb + ions [12], using FT-ICR combined with classical avoided crossing [13]. In this publication we study the first coupling observed between trapped ions and a quartz resonator, even when the resonator is at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, using Eqs. (12) and (17), Ω + m = 3.00458 × Ω − m for a balanced crystal. In addition, from Fig.…”
Section: A Measurement Schemementioning
confidence: 99%
“…Such an approach would also benefit precise mass measurements that are required in the context of neutrino physics where often the mass of rare isotopes, available only in limited samples, are demanded. The limitation in sen-sitivity of the Phase-Imaging Ion-Cyclotron-Resonance (PI-ICR) technique, currently in use at GSI-Darmstadt, to about 10 ions [10] motivated the development of new techniques [11,12].…”
Section: Introductionmentioning
confidence: 99%